2018
DOI: 10.1002/ejsp.2364
|View full text |Cite
|
Sign up to set email alerts
|

Admissions of racism in discourse on migration in Greece: Beyond the norm against prejudice?

Abstract: The turn to language in social psychology is closely related to the study of prejudice as racist discourse has been the subject matter of some of the ground‐breaking discourse analytic work. A widely accepted argument was that there seems to be a norm against prejudice informing Western societies: people commonly engage in denials of prejudice when they make negative comments about minorities. Recent work has argued that, due to ideological shifts in the wider societal context or because denying prejudice may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Sapountzis et al (2006) found that speakers also flexibly managed their category use so as to avoid appearing prejudiced, while also presenting immigrants as aggressive or prone to criminality, which is a consistent representation of migrant groups (see Figgou, Sapountzis, Bozatzis, Gardikiotis, & Pantazis, 2011;Goodman & Speer, 2007;Leudar, Hayes, Nekvapil, & Turner Baker, 2008). However, more recent work by Xenitidou and Sapountzis (2018) has suggested that in talk about migration, people are now more willing to make admissions of prejudice and racism, but do so ironically in ways that still adhere to the cultural norm against prejudice, while criticising the norm against prejudice.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sapountzis et al (2006) found that speakers also flexibly managed their category use so as to avoid appearing prejudiced, while also presenting immigrants as aggressive or prone to criminality, which is a consistent representation of migrant groups (see Figgou, Sapountzis, Bozatzis, Gardikiotis, & Pantazis, 2011;Goodman & Speer, 2007;Leudar, Hayes, Nekvapil, & Turner Baker, 2008). However, more recent work by Xenitidou and Sapountzis (2018) has suggested that in talk about migration, people are now more willing to make admissions of prejudice and racism, but do so ironically in ways that still adhere to the cultural norm against prejudice, while criticising the norm against prejudice.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
“…However, alternative categories that distinguished between immigrant groups deemed either able or unable to integrate into Greece were also used, which provided the rationale for excluding certain groups. However, more recent work by Xenitidou and Sapountzis (2018) has suggested that in talk about migration, people are now more willing to make admissions of prejudice and racism, but do so ironically in ways that still adhere to the cultural norm against prejudice, while criticising the norm against prejudice. However, more recent work by Xenitidou and Sapountzis (2018) has suggested that in talk about migration, people are now more willing to make admissions of prejudice and racism, but do so ironically in ways that still adhere to the cultural norm against prejudice, while criticising the norm against prejudice.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
“…An explicit denial attends to the possibility that a speaker might be heard as having an irrational and thereby prejudiced disposition towards the group being described (e.g. Billig, 1988;Goodman, 2014;McKinlay & McVittie, 2008;van Dijk, 1992;Xenitidou & Sapountzis, 2018). For example, in a study of how white US college students mobilise criticisms of fellow (black) students, Foster (2009) notes that participants commonly deny that their complaints are grounded in race.…”
Section: Inoculationmentioning
confidence: 99%
“…However, rhetorical constructions are not rhetorically potent by nature but should be worked up as factual and realistic, with speakers often employing psychological concepts to manage issues of stake and accountability (Edwards & Potter, 1992;Potter, 1996). For example, researchers have explored the rhetorical resources that social actors often mobilize to account for certain phenomena such as racism (Wetherell & Potter, 1992;Xenitidou & Sapountzis, 2018) and asylum seeking (Burke & Goodman, 2012;Every & Augoustinos, 2008;Kirkwood, Goodman, McVittie, & McKinlay, 2016). This strand of research also offers useful insights into the ways that social actors attend to and negotiate dilemmas of stake (Potter, 1996) and broader ideological dilemmas (Billig et al, 1988;Wetherell, 1998), such as the articulation of racist positions with the parallel disavowal of racism for oneself.…”
Section: Constructing Social Problems and Identitymentioning
confidence: 99%